Association between increased blood interleukin-6 levels on emergency department arrival and prolonged length of intensive care unit stay for blunt trauma. Issue 1 (December 2016) - Taniguchi, Masashi; Nakada, Taka-aki; Shinozaki, Koichiro; Mizushima, Yasuaki; Matsuoka, Tetsuya
Abstract Background Systemic immune response to injury plays a key role in the pathophysiological mechanism of blunt trauma. We tested the hypothesis that increased blood interleukin-6 (IL-6) levels of blunt trauma patients on emergency department (ED) arrival are associated with poor clinical outcomes, and investigated the utility of rapid measurement of the blood IL-6 level. Methods We enrolled 208 consecutive trauma patients who were transferred from the scene of an accident to a level I trauma centre in Japan and admitted to the intensive care unit (ICU). Blood IL-6 levels on ED arrival were measured by using a rapid measurement assay. The primary outcome variable was prolonged ICU stay (length of ICU stay > 7 days). The secondary outcomes were 28-day mortality, probability of survival and Abbreviated Injury Scale (AIS) scores. Results Patients with prolonged ICU stay had significantly higher blood IL-6 levels on ED arrival than the patients without prolonged ICU stay (P  < 0.0001). The receiver-operating characteristic curves produced an area under the curve of 0.75 (95 % confidence interval [CI], 0.66–0.84;P  < 0.0001) for prolonged ICU stay. The patients who had increased blood IL-6 levels on ED arrival had increased 28-day mortality (P  = 0.021) and decreased probability of survival (P  < 0.0001). The AIS scores for the thorax, abdomen, extremity, and external body regions independently correlated with blood IL-6 levels (unstandardized coefficients [95 % CI] for the thorax: 23.8 [12.6–35.1];P  < 0.0001; abdomen: 42.7 [23.8–61.7];P  < 0.0001; extremity: 19.0 [5.5–32.4];P  = 0.0060; external body regions: 62.9 [13.2–112.7];P  = 0.030); the standardized coefficients for the thorax (0.27) and abdomen (0.28) were larger than those for the extremity (0.18) and external body regions (0.15). Conclusions Increased blood IL-6 level on ED arrival was significantly associated with prolonged length of ICU stay. Blood IL-6 level on ED arrival independently correlated with the AIS scores for the abdomen and thorax, and, to a lesser extent, those for the extremity and external body regions. The rapid measurement of blood IL-6 level on ED arrival can be utilized as a fast screening tool to improve assessment of injury severity and prediction of clinical outcomes in the initial phase of trauma care.